2021
DOI: 10.1111/bjh.17379
|View full text |Cite
|
Sign up to set email alerts
|

Reduced intensity allogeneic hematopoietic stem cell transplantation is a safe and effective treatment option in high‐risk myeloma patients – a single centre experience

Abstract: Allogeneic stem cell transplantation (allo-SCT) has been extensively investigated as a potentially curative treatment strategy for myeloma. Early studies using myeloablative conditioning showed an unacceptable transplant-related mortality (TRM) of 53%, despite long-term remission rates (39%). 1 Recent improvements in transplant conditioning, graft-versus-host disease (GvHD) prophylaxis and treatment, and supportive care have seen allo-SCT for myeloma re-emerge as a viable option, in particular for young patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In various studies remission status at allo-SCT was also a relevant predictor for survival with significantly longer OS and/or PFS in patients responding to induction as compared to those with progressive disease at the time point of transplantation [ 17 , 18 , 36 , 43 , 45 , 51 , 67 , 75 , 77 , 78 , 80 , 81 , 82 ]. The role of minimal residual disease (MRD)-status was analyzed in the post-transplant setting and is not conclusively clarified at this time: Achievement of MRD-negativity by flow cytometry after transplantation led to a survival benefit in a large retrospective analysis [ 76 ], whereas another trial could not prove a difference [ 82 ].…”
Section: Prognostic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In various studies remission status at allo-SCT was also a relevant predictor for survival with significantly longer OS and/or PFS in patients responding to induction as compared to those with progressive disease at the time point of transplantation [ 17 , 18 , 36 , 43 , 45 , 51 , 67 , 75 , 77 , 78 , 80 , 81 , 82 ]. The role of minimal residual disease (MRD)-status was analyzed in the post-transplant setting and is not conclusively clarified at this time: Achievement of MRD-negativity by flow cytometry after transplantation led to a survival benefit in a large retrospective analysis [ 76 ], whereas another trial could not prove a difference [ 82 ].…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…In line with a suspected higher GvM effect, occurrence of mild or moderate chronic GvHD led to a survival benefit [ 52 , 62 , 67 , 72 , 74 ]. On the contrary, the outcome was worse in patients developing severe acute GvHD, likely due to prolonged immunosuppression and increased TRM [ 52 , 71 , 73 ].…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…However, the dissection of the subgroup of patients who may benefit from alloSCT from those who may benefit from less toxic novel agent approaches remains crucial [52]. Limited evidence points to subgroups with high-risk MM patients, young and motivated patients [53][54][55]. Moreover, DLI application is a complex procedure, whereby many factors need to be considered (e.g., patient-oriented factors prior to application, disease-specific factors, as well as possible combinations with further therapies during and after DLI).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in this cohort, the development of chronic GvHD predicted longer survival. ( 50 ) Conversely, the efficacy of allo-HSCT is limited in patients who have active disease at transplantation (median PFS and OS of 6 months and 23 months, respectively) as well as in those patients with early relapse (<12 months) after first-line treatment. ( 51 53 ) Compared with non-transplantation approaches, an Italian retrospective study showed a potential benefit for allo-HSCT in RRMM.…”
Section: Allogeneic Hsct In Relapsed/refractory Multiple Myelomamentioning
confidence: 99%